A Case of Autoimmune Hemolytic Anemia after the First Dose of COVID-19 mRNA-1273 Vaccine with Undetected Pernicious Anemia. (29th January 2022) - Jaydev, Fnu; Kumar, Vinod; Khatri, Jaikumar; Shahani, Shobha; Beganovic, Sead
Abstract : By this time, multiple vaccines have been approved to limit the spread of SARS-CoV-2 worldwide. These include new-generation vaccines that contain mRNA of the target organism. Some common side effects were identified and reported during phase 3 clinical trials of vaccination, but more rare adverse events were reported in the literature. One such concern is autoimmune conditions that SARS-CoV-2 viral antigens could have possibly incited. We are presenting here a case of a young female with no known autoimmune diseases, diagnosed with autoimmune hemolytic anemia about a week after receiving her first dose of the COVID-19 mRNA vaccine. We discuss the possible culprit for precipitation of autoimmune hemolytic anemia after the SARS-CoV-2 mRNA vaccine, which encodes virus spike protein. This case highlights the importance of being vigilant for identifying rare adverse events that could appear during mass vaccination.